Comment traduire l’inexistant: définitude/indéfinitude des syntagmes binominaux - Karolak, Stanisław (Studia Romanica Posnaniensia, 2007)
The article deals with the problem of criteria to be followed in the translation of Slavic noun phrases that have no overt markers of definiteness/indefiniteness into a language with articles. It is affirmed that the category of semantic defmiteness/indefiniteness is not restricted to languages with articles and therefore the initial criterion is furnished by sense, or more precisely, by the relations between the intention of the noun phrase and the intention determined by its position. These relations determine intentional completeness or incompleteness, tantamount to definiteness and indefiniteness, respectively. Because of the fact that there is no one-to-one correspondence between semantic definiteness or indefiniteness and their surface reflexes, the translator must furthermore follow the idiomatic rules that govern the assignment of definiteness markers to particular semantic categories. Selected parallelisms between semantic and formal rules are illustrated with equivalences between Slavic (Polish and Russian) noun phrases and their translations in French.